Endocrine disrupting chemicals: harmful substances and how to test them - Olea-Serrano Nicolás; Fernández-Cabrera Mariana F.; Pulgar-Encinas Rosa; Olea-Serrano Fátima (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
This paper presents an analysis of the opinions of different groups from: scientists, international regulatory bodies, non-governmental organizations and industry; with an interest in the problem of identifying chemical substances with endocrine disrupting activity. There is also discussion of the consequences that exposure to endocrine disruptors may have for human health, considering concrete issues related to: the estimation of risk; the tests that must be used to detect endocrine disruption; the difficulties to establish an association between dose, time of exposure, individual susceptibility, and effect; and the attempts to create a census of endocrine disruptors. Finally, it is proposed that not all hormonal mimics should be included under the single generic denomination of endocrine disruptors.